2007
DOI: 10.1007/s10903-007-9054-x
|View full text |Cite
|
Sign up to set email alerts
|

Hmong Adults Self-Rated Oral Health: A Pilot Study

Abstract: Since 1975, the Hmong refugee population in the U.S. has increased over 200%. However, little is known about their dental needs or self-rated oral health (SROH). The study aims were to: (1) describe the SROH, self-rated general health (SRGH), and use of dental/physician services; and (2) identify the factors associated with SROH among Hmong adults. A cross-sectional study design with locating sampling methodology was used. Oral health questionnaire was administered to assess SROH and SRGH, past dental and phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
4
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 21 publications
4
23
4
2
Order By: Relevance
“…Bivariate analysis showed that being female, having regular dental attendance, having health insurance, bad SRH, older age, being married, and having lower natural teeth were strongly associated with good SROH. In contrast to previous studies (Gift et al, 1998;Kim et al, 2010;Okunseri et al, 2008b;Reisine & Bailit,1980), we found that older adults were more likely to rate their oral health better than younger adults. Consistent with previous studies (Patussi et al, 2010;Reisine & Bailit, 1980), we found that males tended to rate their oral health worse than females.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Bivariate analysis showed that being female, having regular dental attendance, having health insurance, bad SRH, older age, being married, and having lower natural teeth were strongly associated with good SROH. In contrast to previous studies (Gift et al, 1998;Kim et al, 2010;Okunseri et al, 2008b;Reisine & Bailit,1980), we found that older adults were more likely to rate their oral health better than younger adults. Consistent with previous studies (Patussi et al, 2010;Reisine & Bailit, 1980), we found that males tended to rate their oral health worse than females.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with previous studies (Abelsen, 2008;Araújo et al, 2009;Camargo et al, 2009;Gilbert et al, 2003;Locker & Miller, 1994;Matos & Lima-Costa, 2006;Maupomé et al, 2004;Okunseri et al, 2008b;Pavi et al, 2010;Petersen et al, 2000;Thomson et al, 2010;Woolfolk et al, 1999;Wu et al, 2011), we found that good SROH was strongly associated with regular dental attendance. It is known that an important part of maintaining good oral health is the use of appropriate dental services (Petersen & Yamamoto, 2005).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations